Systematic Investigation of Products Formed During Synthesis of Ni, W, Cu/Kieselguhr Catalyst by X-ray Diffraction - Srivastava, Tanuja; Saxena, D.C. (Asian Journal of Chemistry, 2012)
Catalytic hydrogenolysis of sucrose is industrially important for the production of glycerol, ethylene glycol and propylene glycol. Nickel(II) catalyst promoted by W and Cu and supported on kieselguhr was synthesized in the aqueous medium by co-precipitating compounds of nickel, copper and tungsten on kieselguhr from solution of their salts using sodium carbonate. The composition of the constituents present along with desired catalyst formed during synthesis has profound impact on its catalytic activity. Therefore, the present study deals with the synthesis and characterization of all the constituents' major and minor products formed during synthesis of catalyst both unreduced and reduced by X-ray diffraction studies. The results indicated the formation of appreciable amount of nickel hydro silicates and small amount of ionic nickel carbonate and nickel carbonate hydrate in the unreduced catalyst. Besides the formation of major product, hetropoly acid and nickel tungsten silicide were also present in the unreduced catalyst. The catalyst was reduced at 600 ºC before carrying the hydrogenolysis reactions and the reduced products were also analyzed for the composition, when the catalyst activity was the maximum. The various chemical reactions involved in the synthesis procedure have been discussed.